Emotional Maturity of Teenagers Who Have Mothers as Single Parents in SMA Negeri 1 Maiwa Enrekang - Faradiba Faradiba; Ariyanti Saleh; Akbar Harisa (Faculty of Nursing, Universitas Hasanuddin, 2016)
Introduction: The high number of divorce in Indonesia would cause big impacts to children. Nowadays, family with single parents used to have specific problems. It is caused by the condition that only one person who grow their child. Most of them, teenagers who loss their fathers in their 11 or 15 years old (teenage middle age) felt emotional distress such us, loneliness, sadness, and lack of attentions. Aims of study is to know about Emotional Maturity of teenagers having Mother as Single Parents in SMA Negeri 1 Maiwa, Enrekang City. Method: This research is a quantitative study with descriptive analytic design. The Sampling Method of this research is Total Sampling. With number of sample is 33 teenagers. Result: this research showed that 93.9% respondents, have a high dependence, 97% of respondents have a high acceptance of reality, 78.8% respondents have skills in right response, 97% of respondents have high safe feeling, and 57% of respondents have high adaptation skills, 100% of respondents have high empathy skill, 66.7% of respondents have high emotion control, therefore 100% of respondents have positive emotional maturity. Conclusion: Most respondents have high emotional maturity (dependence, acceptance of reality skill, right response skill, safe feeling, adaptation skill, empathy skill, and emotion control skill). Therefore, it could be new information about teenage emotional maturity from those having mothers as single parents, and hopefully this study could help and build maturity of teenagers in SMA Negeri 1 Maiwa, Enrekang City.